2009
DOI: 10.1007/s00192-009-1038-z
|View full text |Cite
|
Sign up to set email alerts
|

Factors used by female pelvic medicine and reconstructive surgery fellowship directors to select their fellows

Abstract: Our results support anecdotal evidence that placed emphasis on research experience and interpersonal skills in the selection of FPM&RS fellows.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
7
1

Year Published

2012
2012
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 6 publications
0
7
1
Order By: Relevance
“…In contrast, Miller et al 11 found that the interview is not taken into account when ranking applicants for surgical fellowship. This is further supported by Muffly et al, 12 who surveyed PDs for FPM&RS fellowships and found that the interview is not an important factor in ranking applicants. Although previous studies 2 , 7 , 17 , 20 support the value of the interview in ranking fellowship applicants, the emphasis placed on the interview itself varies depending on the type of fellowship.…”
Section: Discussionmentioning
confidence: 65%
See 1 more Smart Citation
“…In contrast, Miller et al 11 found that the interview is not taken into account when ranking applicants for surgical fellowship. This is further supported by Muffly et al, 12 who surveyed PDs for FPM&RS fellowships and found that the interview is not an important factor in ranking applicants. Although previous studies 2 , 7 , 17 , 20 support the value of the interview in ranking fellowship applicants, the emphasis placed on the interview itself varies depending on the type of fellowship.…”
Section: Discussionmentioning
confidence: 65%
“… 6 Several studies have evaluated factors considered to be most important in ranking those applying to a variety of medical and surgical fellowships. 4 , 7 , 8 , 11 13 , 15 Although the most important factors tend to be similar across different fellowship programs, 7 , 10 , 13 the emphasis placed on some factors can vary depending on the specific fellowship program. In 2010, Muffly et al 12 surveyed directors of fellowships for female pelvic medicine and reconstructive surgery (FPM&RS) regarding factors considered to be important in their ranking process.…”
mentioning
confidence: 99%
“…This is reflected in the number of publications across multiple specialties that deal with resident selection criteria. [2][3][4] This study complements a recent publication 5 by our group that investigated the criteria applicants used in selecting an OHNS residency program. This study found significant differences between what applicants chose as the most important criteria in selecting a residency program and what those programs expected.…”
mentioning
confidence: 84%
“…14 The category of educational data included items related to quality of medical education and research experience. Prematch preparation focused on previous publications and participation in fellowship visiting electives.…”
Section: Methodsmentioning
confidence: 99%